Structural Evolution of Silicon Carbide Nanopowders during the Sintering Process. (20th March 2014) - Volkova, Galina; Doroshkevych, Oleksandr; Shylo, Artem; Zelenyak, Tetyana; Burkhovetskiy, Valeriy; Danilenko, Igor; Konstantinova, Tetyana
Abstract : Processes of sintering of silicon carbide nanopowder were investigated. Values of density (ρ = 3.17  g/cm 3 ) and strength (σ = 450  MPa) were obtained. Within the theory of dispersed systems, the temperature evolution of the materials structure was considered. The relationship between sintering temperature, characteristics of crystal structure and physical properties, in particular, density, and strength of aforementioned ceramics was established. It was concluded that it is necessary to suppress the anomalous diffusion at temperatures above 2080°C.